Development of the Supported Employment, Comprehensive Cognitive Enhancement, and Social Skills program for adults on the autism spectrum: Results of initial study. (January 2018) - Baker-Ericzén, Mary J; Fitch, Meghan A; Kinnear, Mikaela; Jenkins, Melissa M; Twamley, Elizabeth W; Smith, Linda; Montano, Gabriel; Feder, Joshua; Crooke, Pamela J; Winner, Michelle G; Leon, Juan
The population of adults on the autism spectrum continues to increase, and vocational outcomes are particularly poor. Longitudinal studies of adults with autism spectrum and without intellectual disability have shown consistent and persistent deficits across cognitive, social, and vocational domains, indicating a need for effective treatments of functional disabilities as each impact employment. This initial pilot study is an open trial investigation of the feasibility, acceptability, and initial estimates of outcomes for the newly developed Su pported Employment, C omprehensive C ognitive E nhancement, and S ocial S kills intervention, a manualized "soft skills" curriculum, to enhance both cognitive and social development in adults with autism spectrum. A total of eight adults with autism spectrum, without intellectual disability (78% males), participated in the study. Results support the original hypothesis that adults with autism spectrum can improve both cognitive (i.e. executive functioning) and social cognitive (i.e. social thinking and social communication) abilities. Further Su pported Employment, C omprehensive C ognitive E nhancement, and S ocial S kills was found to be feasible, acceptable, and highly satisfactory for participants and parents. Employment rates more than doubled post-intervention, with an increase from 22% to 56% of participants employed. Conclusion is that Su pported Employment, C omprehensive C ognitive E nhancement, and S ocial S kills has promise as an intervention that can be easily embedded into exiting supported employment vocational training programs to improve cognitive, social, and vocational outcomes.